Dynamics of bacterial biofilm development imaged using light sheet fluorescence microscopy - Šmerdová, Lenka; Füzik, Tibor; Valentová, Lucie; Bárdy, Pavol; Procházková, Michaela; Pařenicová, Martina; Plevka, Pavel (Biochemistry and biophysics reports, 2025)
Biofilm formation exacerbates bacterial infections and interferes with industrial processes. However, the dynamics of biofilm development, especially if formed by a combination of more than one species, is not entirely understood. Here, we present a microfluidic cultivation system that enables continuous imaging of biofilm growth using light sheet fluorescence microscopy (LSFM). We studied the development of biofilms of the human pathogens Staphylococcus aureus and Pseudomonas aeruginosa. Multidirectional LSFM imaging enables the calculation of a three-dimensional reconstruction of the biofilm structure with isotropic resolution. Whereas S. aureus forms 50-70-μm-thick mushroom-like structures, a P. aeruginosa biofilm is 10-15 μm thick with cell clusters 25 μm in diameter. A combined biofilm resulted in the formation of large mushroom-like clusters of S. aureus cells that were subsequently dispersed by invading P. aeruginosa. A higher inoculation ratio favoring P. aeruginosa resulted in the formation of small and stable S. aureus clusters overgrown with P. aeruginosa cells. Applying conditioned media from S. aureus and P. aeruginosa coculture to a single-species S. aureus biofilm induced its dispersion. Integrating a microfluidic system into LSFM enables the visualization of biofilm formation dynamics and the effects of compounds on biofilm development.